Biomarkers for acute and chronic graft versus host disease: state of the art. Issue 1 (2nd January 2021) - Giaccone, Luisa; Faraci, Danilo Giuseppe; Butera, Sara; Lia, Giuseppe; Di Vito, Clara; Gabrielli, Giulia; Cerrano, Marco; Mariotti, Jacopo; Dellacasa, Chiara; Felicetti, Francesco; Brignardello, Enrico; Mavilio, Domenico; et al.
ABSTRACT: Introduction: Despite significant advances in treatment and prevention, graft-versus-host disease (GVHD) still represents the main cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Thus, considerable research efforts have been made to find and validate reliable biomarkers for diagnosis, prognosis, and risk stratification of GVHD. Areas covered: In this review the most recent evidences on different types of biomarkers studied for GVHD, such as genetic, plasmatic, cellular markers, and those associated with microbiome, were summarized. A comprehensive search of peer-review literature was performed in PubMed including meta-analysis, preclinical and clinical trials, using the terms: cellular and plasma biomarkers, graft-versus-host disease, cytokines, and allogeneic hematopoietic stem cell transplantation. Expert opinion: In the near future, several validated biomarkers will be available to help clinicians in the diagnosis of GVHD, the identification of patients at high risk of GVHD development and in patients' stratification according to its severity. Then, immunosuppressive treatment could be tailored to each patient's real needs. However, more efforts are needed to achieve this goal. Although most of the proposed biomarkers currently lack validation with large-scale clinical data, their study led to improved knowledge of the biological basis of GVHD, and ultimately to implementation of GHVD treatment.